Investigation of The DNA Damage of White Blood Cell in Cancer Patients Under Chemotherapy and Normal People - Sakib, S M Nazmuz (Asian Pacific Journal of Cancer Nursing, 2025)
Based on the results obtained in this experiment, this report suggests that the alkaline comet assay is a highly sensitive exposure biomarker that plays an active role in the rapid and easy detection of primary DNA damage in leukocytes of specific patients can be concluded to be one of play with cancer. However, a few steps should be used to ensure the best approach to the subject is achieved. Based on the information presented in this review, using small white whole blood successes is the best approach as it is a simple and non-traumatic method of sampling. Makes the assay suitable for conventional applications in human biomonitoring. In conjunction with standard cytogenetic endpoints, we take responsibility for providing a clinically robust diagnostic approach for the routine detection of significant lesions occurring in leukocytes after delivery of antineoplastic agents.